Shortening post-processing and improving forming quality of holes in laser shock punching with the aid of silicone rubber. (October 2018) - Song, Libin; Zhang, Xiu; Zhang, Yiliang; Li, Heng; Ji, Zhong; Zheng, Chao
Highlights: Using rubber can avoid the post-treatment and shorten the whole punching process. Dimensional accuracy of punched holes is remarkably improved using rubber sheet. Heightened shape accuracy of holes is achieved by rubber in laser shock punching. The fracture mechanism is unchanged in laser shock punching process with rubber. Abstract: The comparative study on the laser shock punching process without and with silicone rubber was carried out in this work. Three levels of laser power densities as well as four various die hole diameters were provided, and then the characteristics of dimensional accuracy, shape accuracy, and fracture surface morphology of punched holes were examined. Based upon experimental results, the effect of silicone rubber sheet on the post-processing and the forming quality of punched holes was analyzed. Compared with laser shock punching without rubber, the application of silicone rubber in laser shock punching process can avoid the additional post-treatment of remaining black paint and thus shorten the whole punching process. However, the fracture mechanism of metal foil is unchanged and still keeps shear fracture in laser shock punching process with the aid of silicone rubber. It is revealed that the dimensional accuracy of punched holes can be remarkably improved using the silicone rubber sheet as a pressure transmitting medium, which is related to the enhanced compressive force from rubber on metal foil. Moreover, the shape accuracy of punched holes is strongly influenced by silicone rubber in laser shock punching process. The measurements indicate that heightened shape accuracy can be achieved with the aid of silicone rubber during punching.